Human Interface and the Management of Information: Information, Design and Interaction 18th International Conference, HCI International 2016 Toronto, Canada, July 17-22, 2016, Proceedings, Part I - Yamamoto, Sakae (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
The two-volume set LNCS 9734 and 9735 constitutes the refereed proceedings of the Human Interface and the Management of Information thematic track, held as part of the 18th International Conference on Human-Computer Interaction, HCII 2016, held in Toronto, Canada, in July 2016. HCII 2016 received a total of 4354 submissions of which 1287 papers were accepted for publication after a careful reviewing process. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas This volume contains papers addressing the following major topics: information presentation; big data visualization; information analytics; discovery and exploration; interaction design, human-centered design; haptic, tactile and multimodal interaction.